Anthropologie et santé en Asie du Sud-Est - Anne Yvonne Guillou; Evelyne Micollier (Moussons, 2010)
Based on both results and prospects, this article traces the gradual construction of a specific field of research, namely, the field of health, disease and care, mainly approached from historical and anthropological viewpoints. By identifying the key research schemes and dynamics of this latter, this work emphasizes significant scientific steps and shifts as well as its major breakthroughs in Southeast Asia. Such lines of research are relatively less explored in this geographical area than others. Following a chronological order in conjunction with a thematic one, while referring to key studies, the article demonstrates the depth and wealth of the debates, as well as the current vitality of this discipline.